Analisis Perhitungan PPH Final UMKM Wajib Pajak Orang Pribadi Sebelum Dan Sesudah Undang - Undang Harmonisasi Peraturan Perpajakan (UU HPP) - Ahmad Try Handoko; Nanda Ladepi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Sustainable tax policy reform is needed to help MSMEs survive and grow in order to contribute more to the economy. The enactment of the Law on Harmonization of Tax Regulations (UU HPP) comes as a breath of fresh air for MSME actors in the HPP Law, where the regulation states that there is Non-Taxable Income (PTKP) for Individual MSME Taxpayers (WP OP UMKM). The problems often experienced by MSME actors who are run by individuals are related to tax regulations that often change, so that WP OP UMKM become less familiar with regulations that often change quickly. This study aims to analyze the comparison of the final PPh burden of MSMEs paid by WPOP before and after the enactment of PP 55 of 2022, as well as to find out whether the subjects in this study are aware of the latest changes regarding the threshold for Final PPh MSMEs.